(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 1995)
Enquiry into the nature and function of language has been the dominant theme of 20th. century philosophy. In this paper I shall concentrate on exploring some of Heidegger’s and Lacan’s ideas about language, which originated in the work of Nietzsche and de Saussure, amongst others. These ideas now extend into every area of the West’s cultural life, and have an increasing influence on the development of psycho-analysis and social theory. After outlining the main theories of these two thinkers I shall explore some of the issues raised by Heidegger’s demand that we ’submit to language’, and his views on the function of language will be contrasted with those of Lacan. Here I shall focus on Lacan’s concept of the unconscious and his view of the human subject. These views will also be discussed with reference to the work of Heidegger, and I shall end by exploring some of their implications for psycho-therapy, with particular reference to the existential tradition.